Mental Health of College Students and Its Relation to Life Satisfaction and Social Media Abuse - Muhammad Defrianto; Alfiasari Alfiasari (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
Adolescents are known for their critical development period due to problems they often face in their daily lives. The problem occurs as a result of adolescent developmental tasks that have not been appropriately fulfilled. One of the problems of adolescents is social media abuse. This study analyzes college students' mental health and their relation to life satisfaction and social media abuse. This research is a quantitative approach that involved 302 college students from the Vocational School of IPB University as respondents. The sampling technique used convenience sampling considering the data is taken online and distributed to as many population members as possible. With this technique, respondents are assumed to be willing to fill out the questionnaire because they feel more comfortable and safer. The results prove that male students in this study more often abuse social media than female students. College student life satisfaction in this study is not related and does not influence mental health and social media abuse. Mental health is proven to be related and influenced by abuse behavior, where an increase in mental health will decrease the tendency of social media abuse on college students.